The impact of varying protein sources on goat growth and feed cost - Mitchell, Allianna R.; Sorensen, Rachel J.; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2018)
Feed is the number one expense for farmers, accounting for 50% of costs. There is minimal research on meat goat diets. Thus, this project is crucial to helping farmers choose the best diet for the goats while minimizing their expenses. The objective of this research is to evaluate the impact of varying protein and acid sources on feedlot goat growth and carcass traits. To test this, seventy-five Boer influenced goats around the same age and starting body weight were randomly allocated to twenty-five different pens (5 pens per treatment/3 goats per pen). The pens were randomly allocated one of the five isocaloric and isonitrogenous diets 1) 18.7% soybean meal (SBM) and 0.75% ammonium chloride; 2) 34.4% distillers’ dried grains (DDGS) and 0.75% ammonium chloride; 3) 22.0% SoyPlus and 0.75% ammonium chloride; 4) 17.2% SBM and 4.83% SoyChlor; 5) 20.0% SoyPlus and 4.83% SoyChlor. Goats were kept on a self-feeder with unlimited access to their dietary treatments and fresh water. The experiment lasted 42 days and the goats were weighed every seven days. Using the first and last weigh data (d0 and d42) ADG, ADFI, and G:F were calculated as well as feed costs. Between all of the diets, there was no statistical difference (P>0.05) in ADG, ADFI, and G:F. All treatments had relatively similar carcass traits (P>0.05). Although no difference was detected in growth and carcass traits, the diets had a statistically significant difference in feed cost ($/goat) (P<0.05). As of September 1, 2018, the diet feed costs ($/goat) were as followed 1) 19.60; 2) 16.07; 3) 18.03; 4) 25.82; and 5) 23.14. Therefore, the preferred diet is treatment two for Boer influenced goats because it has the lowest feed cost and goats will grow the same as more expensive diets.
Keywords: Fall 2018